Efektivitas Modul Speaking Affective Filter Untuk Menurunkan Kecemasan Pada Murid Usia 9-12 Tahun Di E-Now Kids Learning Center - Astriyanie Nurfitri Arifuddin; Ahmad Razak; Sitti Murdiana (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2024)
The languages used by humans are very diverse, so humans need a means or "bridge" to unite their ideas or opinions, such as English. English is the most widely studied foreign language in Indonesia. This study aims to determine the effectiveness of the Speaking Affective Filter module in reducing anxiety in students aged 9-12 years at the e-now kids learning center. This research uses a qualitative descriptive method with a literature research approach, combined with an experimental method to investigate the effect of specific treatments. The research was conducted over five meetings in May-June 2024. The research population consists of students participating in the Kids Speaking Program at E Now Kids Learning Center. Therefore, the population includes all elements of the objects/subjects being studied, while the sample in this study is 30 students selected through purposive sampling. The data analysis technique used in this research is descriptive analysis. Based on the results and discussions explained regarding the effectiveness of the speaking affective filter module in reducing anxiety among students at the e-now kids learning center, it can be concluded that the speaking affective filter module is effective in reducing English language anxiety in students aged 9-12 years at E-Now Kids Learning Center.